2016
DOI: 10.17795/ajdr-25275
|View full text |Cite
|
Sign up to set email alerts
|

How Useful is the AgNOR Staining Method for the Diagnosis of Salivary Gland Tumors?

Abstract: Objectives: The purpose of this study was to determine the numbers and mean areas of the AgNOR dots in the 3 most common salivary gland tumors. Materials and Methods: One hundred and seventy paraffin blocks histologically diagnosed as pleomorphic adenoma, adenoid cystic carcinoma, and mucoepidermoid carcinoma were selected from the archives of the pathology department of Loghman hospital, Tehran, Iran and then cut and stained using the standard AgNOR method. The number and area of AgNOR dots were evaluated. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…The AgNORs were numerous and pleomorphic in ACC. This finding is compatible with the study done by Irani et al, (2016), who detected significant differences between the type of tumor and AgNOR, with ACC having the highest AgNOR number (Irani et al, 2016). These findings contradict the findings of Adeyemi et al, study (2006), which showed no significant difference in their mean AgNOR value and different histological types.…”
Section: Discussionsupporting
confidence: 85%
“…The AgNORs were numerous and pleomorphic in ACC. This finding is compatible with the study done by Irani et al, (2016), who detected significant differences between the type of tumor and AgNOR, with ACC having the highest AgNOR number (Irani et al, 2016). These findings contradict the findings of Adeyemi et al, study (2006), which showed no significant difference in their mean AgNOR value and different histological types.…”
Section: Discussionsupporting
confidence: 85%
“…[ 3 ] Regarding the histopathology, MECs are classified as low, intermediate, and high grade according to the relative number of epidermoid, mucous, and intermediate cell types, growth pattern, type of invasion, and cytological atypia. [ 2 4 5 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…Pleomorphic adenoma (PA) is the most common benign salivary gland tumor, constituting 45% to 85% of all major and minor salivary gland tumours. [ 1 2 ] It has been suggested that PA arises from myoepithelial cell and ductal cell differentiation into mesenchymal and epithelial structures. It is also believed that PA originates from reserve cells or stem cells of intercalated ducts which differentiate to mesenchymal and epithelial cells which may explain morphological diversity in PA, but the initiation factors of tumor progression are not fully understood.…”
Section: Introductionmentioning
confidence: 99%